The influence of color on ergonomics: architecture and urbe - Demarchi, Ana Paula Perfetto (2021)
This article reports on the interrelation of Cognitive Ergonomics with Architecture and Urbanism, mainly in the use of urban parks and the correlation with the use of colors. The conduction of the search involved the use of Qualitative Research with the collection of the spontaneous reports of the Alambari Park users. After this stage, we applied questionnaires based on the Likert Scale. Thus, it was possible to reach a diagnosis of the research and propose suggestions for the park.